Synthesized Vortex Beams in the Turbulent Atmosphere - Aksenov, Valerii P.; Dudorov, Vadim V.; Kolosov, Valeriy V.; Levitsky, Mikhail E. (Frontiers in Physics, 2020)
The results of our investigations on the control over the orbital angular momentum (OAM) of a laser beam synthesized through combination of wave fields of a fiber array are reviewed. Peculiarities of OAM formation in the case of control over the value of phase shifters of individual sub-beams are studied theoretically and experimentally. The conditions for formation of vortex beams with the given value of the orbital angular momentum are determined. The information coding by the OAM value is demonstrated in laboratory experiments. Statistical characteristics of vortex Laguerre—Gaussian and synthesized laser beams propagating through the turbulent atmosphere are studied theoretically. Versatile models are proposed for the probability density function of radiation intensity fluctuations in the cross section of an arbitrary-type beam propagating through turbulence of different strength. The spectrum of azimuthal modes of the synthesized vortex beam at its formation and propagation is analyzed.